Trends in industrialization and commercialization of IgY technology - Yakhkeshi, Saeed; Wu, Rao; Chelliappan, Brindha; Zhang, Xiaoying (Frontiers in Immunology, 2022)
IgY technology, which refers to the strategic production process in generating avian immunoglobulin (IgY) against target antigens, is a cost-effective technology with broad applications in the fields of diagnostic, prophylactic, and therapeutic for both human and veterinary medicine. Over the past decade, promising progress was witnessed with the increased registered companies manufacturing IgY products, the number of patents, and the significant number of clinical trials underway. Hence, it is time to performing an overview and prospective analysis of the marketing potential and commercialization of IgY products for large-scale applications. Our review showed that based on the number of patent applications, which is an indicator of innovations, a steep increase is noticed after 2010, with the highest of 77 patents in 2021. In addition, it was found that 73 companies are associated with IgY marketing, of which 27 were identified in the biotherapeutics field for human or veterinary medicine and 46 in the diagnostic field. IgY antibodies were included in the research as a primary and secondary antibody with 3729 and 846 products respectively. The biotherapeutic products have significantly increased as a food supplement or topical use, rather than as parenteral administrations and licensed drugs, due to the lack of technicaln standards established for IgY registration and industrialization, as well as the restriction of the nature of polyclonal antibodies. The R&D on functional IgY fragments is ongoing, indicating a promising area of IgY application. Such retrospective analysis and speculation are necessary for better industrialization and commercialization of IgY technology.